Mental health in pandemic times: what is the impact of Covid-19? - Pinheiro, Guilherme Emanuel Weiss; Kocourek, Sheila (Revista Cuidarte, 2020)
This article is a critical and reflective construction around the current scenario of the coronavirus pandemic and the influence that this situation has on mental health. In addition, it discusses the importance of universal health systems and the focus on actions to promote mental health in this period. It is understood that it is necessary to reflect on these issues, especially in this moment so delicate and dangerous that society lives. This essay aims to encourage discussions and guide new strategies for promoting mental health. How to cite this article: Pinheiro, Guilherme Emanuel Weiss; Kocourek, Sheila. Saúde mental em tempos de pandemia: qual o impacto do Covid-19?. Revista Cuidarte. 2020;11(3):e1250. http://dx.doi.org/10.15649/cuidarte.1250